The Impact of Syrian Refugees on Natives' Labor Market Outcomes in Turkey: Evidence from a Quasi-Experimental Design - Evren Ceritoglu; H. Burcu Gurcihan Yunculer; Huzeyfe Torun; Semih Tumen (Institute for the Study of Labor (IZA), 2015)
Civil war in Syria, which started in March 2011, has led to a massive wave of forced immigration from the Northern Syria to the Southeastern regions of Turkey. This paper exploits this natural experiment to estimate the impact of Syrian refugees on the labor market outcomes of natives in Turkey. Using a difference-in-differences strategy, we find that immigration has considerably affected the employment outcomes of natives, while its impact on wage outcomes has been negligible. We document notable employment losses among informal workers as a consequence of refugee inflows. The majority of those who lost their informal jobs have either left the labor force or remained unemployed. Overall, unemployment rates have increased, while labor force participation, informal employment, and job finding rates have declined among natives. Disadvantaged groups – i.e., females, younger workers, and less-educated workers – have been affected the worst. The prevalence of informal employment in the Turkish labor markets has amplified the negative impact of Syrian refugee inflows on natives' labor market outcomes.
Keywords: J15; J21; J46; J61; C21; 330; informality; labor market; Turkey; immigration; Syrian civil war; difference in differences